Description of Level Education and Employment of Nagari Gurun Panjang Induk Community, Bayang District, Pesisir Selatan District - Yulizawati yulizawati; Yogi Afritunando (Universitas Andalas, 2023)
Population development without being balanced with controls to measure the desired population will only cause social, economic problems with all the high population growth from year to year requiring investment and facilities in the fields of education, health, employment, housing, and so on. This of course will be a quite complicated problem for the government in building and improving the standard of living for the country. Methods this research is study eksploratif with primary and secondary data. Populasi is citizen at nagari gurun panjang induk community. The sample is total sampling. The highest percentage of community work is housewives 23.5%. Te percentage of education in the community is high school 38.6%. In a simple sense, education is a human effort to develop his personality in accordance with the values in society and culture. The level of community education can affect the level of employment, this is evidenced by the percentage of housewives who do not work which is higher than other jobs, while at the level of education, the average community only has education up to high school level